2005
DOI: 10.1503/cmaj.050445
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and risk factors for childhood overweight and obesity

Abstract: CMAJ 2005;173(6):607-13 We measured standing height to the nearest 0.1 cm after students had removed their shoes and body weight to the nearest 0.1 kg on calibrated digital scales. Overweight and obesity were defined using the international body mass index cut-off points established for children and youth. 26 These cut-off points are based on healthrelated adult definitions of overweight (≥ 25 kg/m 2 ) and obesity (≥ 30 kg/m 2 ) but are adjusted to specific age and sex categories for children. 26The CLASS s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
232
7
17

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(279 citation statements)
references
References 36 publications
23
232
7
17
Order By: Relevance
“…As in the present study, previous results on school lunch consumption relative to weight status have mostly shown no relationship (16)(17)(18)(19)(20) . Previous studies that focus only on dinner are lacking.…”
Section: Discussioncontrasting
confidence: 70%
“…As in the present study, previous results on school lunch consumption relative to weight status have mostly shown no relationship (16)(17)(18)(19)(20) . Previous studies that focus only on dinner are lacking.…”
Section: Discussioncontrasting
confidence: 70%
“…§ For details of subjects, see p. 211. Benton, 2004;Veugelers & Fitzgerald, 2005), concluding that parental overweight is the most potent risk factor for childhood obesity. Treuth and colleagues found that a stepwise increase in gains in fat mass and percentage body fat over time occurred with increasing parental body weight status (Treuth et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Parents may be responsible for the overconsumption of cooking oil by children. Parents' socioeconomic status also has an important effect on childhood obesity (Veugelers & Fitzgerald, 2005). Being nationally representative and comprising both diet and physical activity information and parental information are strengths of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Activities based on aerobic exercise have a greater benefit to the general health of children, other than bone health which requires higher-impact physical activities (Veugelers, & Fitzgerald, 2005).…”
Section: Volume 13 | Issue 2 | 2018 | 425mentioning
confidence: 99%